Assessment of public opinion on the use of herbal medicine for the treatment of sexually transmitted infections (STI) in accra - Frank Kwasikumah; Emmanuel U. Osisiogu; Philip Asumang; Amponsah Collins (Traditional Medicine and Modern Medicine)
The use of herbal medicine for treating sexually transmitted infections (STIs) is increasing, especially in developing countries like Ghana. However, little is known about public knowledge and attitudes towards using herbs for STIs. This cross-sectional study aimed to assess awareness of STIs and confidence in herbal medicines for treating STIs among the public in Accra, Ghana. Questionnaires were administered to 383 randomly selected respondents aged 15–49 years. Most respondents first learned about STIs in school and had good knowledge about the causes (bacteria, viruses, etc.), modes of transmission (sexual contact, mother-to-child), and body parts affected (sex organs) by STIs. However, under half of respondents had used herbs to treat STIs in the past 12 months, with over half unable to recall which specific herbs they had taken. Herbal medicine was commonly recommended by friends and family rather than healthcare professionals. Despite limited endorsement from medical practitioners, respondents expressed high confidence in herbal medicine, agreeing that herbs are effective for treating STIs and have the advantage of being low cost. Of respondents who had used herbs for STIs, two-fifths reported being cured, although a small proportion noted long treatment times, persistence of symptoms after treatment, or side effects. Statistical analysis revealed a strong positive correlation between confidence in herbal medicine and its use, but no association between knowledge of STIs and use of herbs for treatment. In summary, while respondents were knowledgeable about STIs, this knowledge did not translate into greater use of herbal medicine. However, user confidence in the effectiveness, safety, affordability, and convenience of herbs for treating STIs was high. More nationwide research is warranted to further understand public attitudes and behaviors towards herbal medicines for STIs in order to inform healthcare policies and educational strategies.